The Effect of Population, Open Unemployment Rate, and Education Level on Poverty in Jambi Province in 2010-2021 - Fathiyah, Fathiyah; Sultoni, Sultoni; Novriana, Heni; Sukmana, Abdi; Aliana, Desita (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Introduction/Main Objectives: This study aims to determine the effect of Population, Open Unemployment Rate and Education Level simultaneously or partially on Poverty in Jambi Province. Research Methods: The statistical analysis employed is multiple linear regression. Finding/Results: This study indicates that the variables of population size, open unemployment rate, and level of education have a significant effect on poverty in Jambi province. Furthermore, the population has a significant effect on poverty, while the open unemployment rate and education level have no effect on poverty. Conclusion: The findings of this study underscore the pivotal role of population in shaping poverty dynamics. While the open unemployment rate and education level do not exhibit a discernible influence on poverty in Jambi Province during the 2010-2021 period, further investigation is warranted to ascertain their potential impact.